Development Trend and Technical Challenges of the Integration of Offshore Wind Turbine with Marine Ranch - Jie YANG; Jianhua ZHANG; Zhaorong MA; Donghua LIU; Hongqing WANG; Ziwei YIN (南方能源建设, 2024)
[Introduction] Under the background of "carbon peak and neutrality" target and "ocean power" strategy, the integration of ocean renewable energy represented by offshore wind power and ocean resources represented by marine ranch is the new direction, new situation and new opportunity for the future development and utilization of ocean resources. The article reviews and analyzes the integrated development mode and key technical problems of offshore wind power and marine pasture, in order to provide technical references to the relevant research and engineering projects in China. [Method] Taking the integration of China's marine resources development needs as the guide, the global development trend of offshore wind power and marine ranch integration was analyzed, and the current situation and shortcomings of China's wind-fishery integration development were clarified. On this basis, the integration mode, equipment design, engineering cases and key technical problems of the integration development of offshore wind power and ocean ranch were analyzed in detail. Finally, a future outlook on the integration development of offshore wind power and ocean ranch in China was discussed. [Result] Through the analysis of the integrated development mode and key technical problems of the integration of offshore wind power and marine ranch development, the bottlenecks and technical challenges are clarified, and the key breakthrough directions are pointed out, providing scientific guidance and reference basis for the comprehensive development and utilization of offshore resources in China. [Conclusion] The article illustrates the necessity and feasibility of integrating the development of offshore wind power and marine ranch, and proposes a feasible way to integrate offshore wind power and marine ranch in China.